Digital Ethics in Islamic Religious Education: Systematic Literature Review - Muksin, Muksin; Afandi, Afandi (Universitas Al-Amien Prenduan, 2025)
This study aims to evaluate the challenges and learning approaches developed in Islamic digital ethics education through a systematic literature review (SLR) method. Digital ethics is urgent in Islamic religious education because students increasingly navigate online spaces filled with misinformation, harmful content, and ethical risks, requiring guidance rooted in Qur’anic and Prophetic values. It ensures that technology supports, rather than undermines, moral character and responsible digital behaviour. The method used follows the Prisma 2020 protocol by analysing 28 selected articles from 327 initial literature identified through national and international databases. The findings show that the main challenges in digital ethics learning include teachers’ low digital literacy, the relevance of the curriculum to contemporary issues, and the absence of a contextual pedagogical approach. The identified learning strategies include integrating Islamic values in digital media case studies, using ethical verse interpretation, and using project-based simulations. This study concludes that there is a need to develop a holistic, standardized, and adaptive Islamic digital ethics learning model that adapts to the dynamics of the digital space. The implications of this study’s results include strengthening the curriculum, teacher training, and the development of technology-based for Islamic learning digital media.